State of a large vessels and microcirculation - a new target for antihypertensive therapy in patients with hypertension and type 2 diabetes - M. E. Statsenko; M. V. Derevyanchenko (Столичная издательская компания, 2017)
Aim. To evaluate the effect of 12 weeks of complex therapy with the fixed combination of enalapril and indapamide on indicators of vascular stiffness of large arteries and parameters of skin microcirculation (MC) in patients with arterial hypertension (HT) and diabetes mellitus (DM) type 2.Material and methods. 30 patients with HT stage II-III in combination with DM type 2 aged 40-70 years were included into the study. The fixed combination of enalapril and indapamide in addition to lipid-lowering and hypoglycemic therapy was prescribed to all patients. Elastic properties of large arteries were assessed by analyzing the pulse wave velocity (PWV) and the calculation of the index of aortic stiffness (IAS). Skin MC and level of glycated hemoglobin (HbA1c) were also determined. Results. After the 12-week treatment all patients reached the target values of blood pressure (BP). Office systolic and diastolic BP levels decreased by 18.8 and 13.1% (p<0.05 for both), respectively. The treatment did not have a negative effect on glucose metabolism - HbA1C concentration decreased by 2.7%. PWV in the vessels of elastic and muscular types decreased by 10.8 and 10.1% (p<0.05 for both), respectively, and IAS decreased by 27.4% (p<0.05). Significant growth in factor myogenic regulation of MC and reduction in bypass indicator by 21.8% were found.Conclusion. Combined therapy with the inclusion of a fixed combination of enalapril and indapamide for 12 weeks had a high antihypertensive efficacy and good tolerability in patients with HT and DM type 2. Treatment significantly reduced the vascular stiffness of large arteries and improved the MC indices in these patients.